MANAJEMEN ASET BADAN USAHA MILIK DESA DI DESA PLEDO KECAMATAN WITIHAMA KABUPATEN FLORES TIMUR - Bernafus Adito MG; Yohanes Demu; Maria P. L. Muga (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2022)
Asset management is a component that must be implemented properly so that an organization or institution can run effectively and efficiently in increasing its revenue. This study was conducted on Village Owned Enterprises (BUMDes) in Pledo Village, Witihama District, East Flores Regency, about how to apply the asset management. The purpose of this study is to describe the storms in which asset management is applied to the Pledo Village Medical and Education Agency in accordance with the theory by Siregar which include several important aspects, namely asset inventory, legal audit, asset valuation, asset optimization, monitoring and control. The type of the research used in this study was qualitative research (Descriptive) with observation technique, interviews and documentation or pict the picture. Based on the results of the study, it can be concluded that asset management of Pledo Village has not yet going well. This is because there is still a lack of competence or insight from human resources regarding good asset management, then the absence of a single audit process that has been carried out, and the absence of required retaliation related to an asset management information system capable of accommodating all activites carried out by BUMDes Pledo.